A Research Support Services for University Libraries in Sri Lanka: Preliminary Web Survey based on Research Lifecycle - Gamage, P.G.M.P. (University of Colombo, 2022)
University academic libraries around the world are increasingly inclined to implement various research support services (RSS) to make it easier for researchers to access quality services. Ideally, libraries should provide RSS addressing researchers’ information needs, embedded in the research lifecycle (RLC). The term "research lifecycle" refers to different stages of the research process, starting from conceiving idea to implementation and to dissemination. An examination of the research literature in Sri Lanka reveals, although some RSS were implemented by university libraries in SL, there was a lack of attention to conducting studies relevant to categories of research support services in Sri Lankan University libraries. Accordingly, the overall aim of this study was to evaluate the RSS of university libraries in SL while investigating the services and its alignment with the RLC. Data were analyzed descriptively and it was concluded that all Sri Lankan university libraries provide RSS, covering all stages of the RLC. Most libraries mainly focused on the 1st (Conception, 100% (n= 15)) and 4th (Preservation and curation, 99.33% (n=14)) stages of the RLC. Under 2nd stage, only one library (University of Colombo, 3, 10%) provided more than two services for “Data processing and analysis” (data analysis guides- webinars, places/ equipment Facilities) and 4 libraries do not offer any services. All libraries surveyed mainly focused only on workshops and webinars, nevertheless, the services such as research data management, GIS support, and supplying tools for data analysis and data management planning were not implemented. Under 3rd stage of the RLC “Publication and sharing” (publication support, citation management guide, providing tools, ORCID and DOI), 9 (24%) and 8 (21%) services are offered by the libraries attached to the University of Kelaniya and University of Colombo respectively. It is worth mentioning that three university libraries do not provide any services under the 3rd stage of the RLC. Therefore, the study concluded that university libraries of Sri Lanka should focus on implementing Research Support Services such as helping to find funding agencies, Special Research Alert services, Digital Mapping and GIS Support, Guides and support for scholarly publications, and ORCID/DOI services. The findings of this study could be used as a guide to improve the research support services of university libraries and make a strong contribution to the research environment.
Keywords: Research Support Services; Research Lifecycle; University libraries